2011
DOI: 10.1007/s10549-011-1494-2
|View full text |Cite
|
Sign up to set email alerts
|

TNF-alpha polymorphisms and breast cancer

Abstract: Tumor necrosis factor-α (TNF-α) is an important pro-inflammatory cytokine in the development and progress in human cancer. TNF-α polymorphisms have been confirmed to influence the risk for several types of cancer, however, the associations between TNF-α polymorphisms and breast cancer (BC) remain controversial and ambiguous. The aim of this meta-analysis is to explore more precise estimations regarding this point. Electronic searches of several databases were conducted for all online publications on the associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 28 publications
3
15
0
Order By: Relevance
“…There have been many reports on the association of TNF-α-308, -238, and -863 with different diseases, such as hepatitis B virus infection (Du et al, 2006;Basturk et al, 2008) and breast cancer (Yang et al, 2011). In our study, we combined the three SNPs and the haplotype association analysis of TNF-α SNPs (-308/-238/-863) showed that the TNF-α AGA haplotype was present at a higher frequency in the OA-TB patients (12.1%) than in the healthy volunteers (3.5%), indicating that it was a risk factor for OA-TB (OR = 4.201, 95%CI = 1.80-9.91, P = 0.010).…”
Section: Discusssionmentioning
confidence: 99%
“…There have been many reports on the association of TNF-α-308, -238, and -863 with different diseases, such as hepatitis B virus infection (Du et al, 2006;Basturk et al, 2008) and breast cancer (Yang et al, 2011). In our study, we combined the three SNPs and the haplotype association analysis of TNF-α SNPs (-308/-238/-863) showed that the TNF-α AGA haplotype was present at a higher frequency in the OA-TB patients (12.1%) than in the healthy volunteers (3.5%), indicating that it was a risk factor for OA-TB (OR = 4.201, 95%CI = 1.80-9.91, P = 0.010).…”
Section: Discusssionmentioning
confidence: 99%
“…In the Mexican population, studies have reported a frequency of 0-8% of the mutant allele (Parra et al, 2006;Sánchez et al, 2008). Although this polymor-phism has been associated with diseases such as rheumatism (Cereda et al, 2012), cardiovascular disease (Chu et al, 2012), diabetes , and cancer (Yang et al, 2011), the results have been inconsistent. The aim of this study was to determine the association between the -308G>A polymorphism in the TNF-α gene and BC in Mexican women.…”
Section: Introductionmentioning
confidence: 99%
“…The TNF-α gene is located within the MHC region on chromosome 6p21.3 (Noguchi et al 2002). Several single-nucleotide polymorphisms have been identified in this region, and the -308G/A polymorphism of the TNF-α gene is the most frequently studied one (Guo et al 2005;Whiteman et al 2010;Yang et al 2011b). It has been illustrated that the G to A nucleotide change at -308 alters the transcription factor binding site, resulting in increased production of TNF-α (Abraham and Kroeger 1999;Elahi et al 2009).…”
Section: Introductionmentioning
confidence: 99%